Diversity of phytoplankton in lower Thu Bon river and Cu Lao Cham - Duyen, Huynh Thi Ngoc; Luom, Phan Tan; Van, Tran Thi Le; Hue, Tran Thi Minh; Lam, Nguyen Ngoc; Hai, Doan Nhu (Vietnam Journal of Marine Science and Technology, 2019)
Data on characteristics of phytoplankton communities is important scientific information in marine ecosystem, especially in assessment of environmental impacts on biodiversity in a specific waters. In the present study, two-year phytoplankton data was analyzed for species diversity, community structure changes and variation in 4 adjacent waters: Lower Thu Bon river (TB), transition waters (CT), Cu Lao Cham island (CLC) and offshore site (BM) to provide basic scientific data of phytoplankton communities, compare and assess seasonal changes and possible linkage of these adjacent waters. A total of 364 phytoplankton taxa of 12 classes were identified, showing high diversity and with seasonal variation of the investigated waters. There was strong difference of phytoplankton communities among the adjacent waters with low similarity index and the change of dominant species seasonally in each area. The species richness and diversity in the lower Thu Bon river were lower than in other areas. Variation of phytoplankton abundance and diversity along the river transect showed changes in species composition between the dry and rainy seasons but with similar trend in abundance. The low community similarity between the adjacent waters and the transition waters may indicate low impacts of river flow on phytoplankton communities in the coastal waters.